Patient experiences with pharmacogenetic testing in a primary care setting. (October 2016) - Haga, Susanne B; Mills, Rachel; Moaddeb, Jivan; Allen Lapointe, Nancy; Cho, Alex; Ginsburg, Geoffrey S
Aim: To investigate patient experiences with pharmacogenetic (PGx) testing.Methods: Patients were offered PGx testing through a study on pharmacist-assisted delivery of PGx testing and invited to complete pre- and post-testing surveys about their experience.Results: Of 63 patients tested, 17 completed the baseline survey (27%). Interest in testing was mostly impacted by desire to inform selection of best treatment (n = 13). Seven of 12 patients that completed the follow-up survey indicated that their provider discussed the test result with them. Five patients understood their test result very or somewhat well. All would be likely to have PGx testing again.Conclusion: Patients perceived PGx testing to be useful, though more effort may be needed to improve patient–provider communication of test results.